Nickel-Catalyzed mesoporous biochar for enhanced adsorptive oxidation of aqueous Sulfide: An investigation of influencing factors and mechanisms. (October 2022) - Abdulbaki Danhassan, Umar; Zhang, Xin; Qi, Riying; Ali, Mahmoud M.; Sheng, Kuichuan; Lin, Hongjian
Graphical abstract: Highlights: BC's K mineral ions and quinone were crucial in the adsorptive oxidation of S 2- . BC used a K + bridge to adsorb S 2- and reached 583 ± 250 mg-sulfide/g maximum capacity. S 2- adsorption on BC is temperature and pH-dependent. S 2- was sorbed onto BC-Ni through mesopores and the K + bridge. Ni 0 dehydrogenates hydroquinone on BC-Ni to produce quinone and H2 O2 for S 2- oxidation. Abstract: Biochar (BC) is a low-cost and electroactive adsorbent for removing sulfide in aqueous media, which toxifies aquatic organisms and corrodes water treatment facilities. However, it lacks a pore structure for sulfide ion (S 2- ) mass transfer to active sites. Herein, it is shown that nickel-modified biochar (BC-Ni) adsorbed S 2- 2.72-fold faster than BC alone and attained a 1244 ± 252 mg-sulfide/g maximum adsorption capacity due to markedly increased mesopores, while BC attained 583 ± 250 mg-sulfide/g. Factors influencing S 2- sorption and theoretical sorption kinetics and isotherms models were evaluated. Structural and surface compositions of BC and BC-Ni were examined using state-of-the-art characterizations. The results suggest that S 2- was adsorbed via pore diffusion, pore filling, and cation bridging and oxidized to elemental sulfur and sulfate with quinone and hydrogen peroxide generated from dehydrogenation of hydroquinone on the BC-Ni by metallic nickel in the carbon matrix. This study would spur biomass valorization and desulfurization.